The Relationship Between Chronic Energy Deficiency (CED) and Adherence to Iron (Fe) Tablet Consumption with the Incidence of Anemia Among Pregnant Women at the Ciputat Timur Community Health Center in 2026 - Handriati, Ade; Nida, Khairun; Cartika, Harpolia (Jurnal Ilmiah Manusia Dan Kesehatan, 2026)
Maternal anemia continues to represent a critical public health issue due to its association with an increased risk of adverse pregnancy outcomes. This study aimed to investigate the relationship between Chronic Energy Deficiency (CED) and adherence to iron (Fe) supplementation in relation to anemia among pregnant women attending the Ciputat Timur District Health Center in 2026. A cross-sectional approach was applied, involving 59 participants selected through total sampling. Data collection was conducted using structured interviews, records from the Maternal and Child Health (MCH) handbook, and verification of antenatal care (ANC) cards. The variables assessed included CED status measured by Mid-Upper Arm Circumference (MUAC), adherence to iron supplementation, and hemoglobin concentration. Statistical analysis using the Chi-square test revealed no significant association between CED and anemia (p = 1.00), while adherence to iron supplementation demonstrated a significant relationship (p = 0.029). The findings highlight that improving compliance with iron intake, supported by nutritional counseling and consistent monitoring, plays a more substantial role in reducing anemia risk than focusing solely on macronutrient status. Therefore, preventive strategies should emphasize sustained adherence to iron supplementation alongside comprehensive maternal health surveillance.. Keywords : Anemia; Pregnant Women; Supplementation Adherence; Chronic Energy Deficiency; Iron Tablets